Pedagogy and Psychology of Modern Education - Iudin G. V., Krasovskaia S. V., Vasiagina T. N., Gorbatov I. A., Ryzhova I. M., Samigullina G. S., Dzokaeva Z. M., Zainullin L. I., Kochetkova T. N., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Prozorova M. N., Boiko A. V., Sesorova L. N., Gani S. V., Konstantinova N. I., Kvitatiani S. V., Zhaldak N. N. (Pedagogy and Psychology of Modern Education, 2023)
in the field of teaching preschool children speech and logical thinking, the problem of transition from spontaneous to purposeful teaching of natural language logic as a conscious method of cognition, especially scientific, is being solved. The logic of a natural language is defined as a system of all its logical means and rules for understanding and using these means. The main research methods are pedagogical experiment, sociolinguistic research and this logic. The author has developed forms of tasks and exercises for targeted teaching from early preschool age to the correct understanding and conscious use of conjunctions, quantifiers, question words and the rules of natural language logic. The forms are shown with the help of which adult parents or educators can themselves understand what is included in this logic and purposefully teach it to children.
Keywords: preschool education; научное познание; целенаправленность; обучение дошкольников; логика естественного языка; осознанный метод; purposefulness; logic of natural language; scientific knowledge; conscious method